(untitled) (Scientific journal of the Fergana State University, 2026)
The article is devoted to the study of the socio-philosophical aspects of the formation of sports as a key phenomenon of modern society at a new stage of its development. The paper reveals the role of sport as a multifaceted phenomenon reflecting major changes, including globalization, technologization, transformation of values and radical medical education. The authors focus on the philosophical concepts of physicality, freedom and social identity, which allow them to better understand the nature of sport as a form of personal and collective self-expression. The study demonstrates the innovativeness of sports in defiance of cultural norms, strengthening social solidarity and promoting the ideas of equality and inclusivity. Special attention is paid to the problems of commercialization of sports, its introduction into the entertainment industry, which often leads to the loss of humanistic foundations. In addition, we consider the challenges of our time related to the use of biotechnology, digitalization and global media exposure. The article has both theoretical and practical significance: the results can be used in the development of strategies for the development of sports, educational programs and research in the field of social philosophy. The works of M.Merleau-Ponty, J.-P. Sartre and modern theories lead to methodological research, which gives it an interdisciplinary character.